MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MELALUI BERMAIN TEBAK GAMBAR PADA ANAK KELOMPOK A1 DI PAUD KEMALA BHAYANGKARI BENGKULU UTARA - Maretha Masyah; Sumarsih Sumarsih; Delrefi D. (Jurnal Ilmiah POTENSIA, 2017)
The purpose of this research is to improve problem solving ability through playing guess figure in children of group A1 in PAUD Kemala Bhayangkari North Bengkulu. The research method used is classroom action research (PTK). The study subjects consisted of twelve children consisting of six girl students and six boy students. Technique of collecting data using observation. Data analysis techniques use the average formula. The results showed an increase in problem solving skills through playing guess figures. It is recommended for further researchers to improve problem solving skills in children by using more interesting media such as by using a variety of images and full color.